Random-walk simulation of non-conservative pollutant transport in shallow water flows. (December 2020) - Yang, Fan; Liang, Dongfang
Abstract: The random-walk method is inherently simple and numerically stable. However, when used in hydro-environmental analyses, most of the existing random-walk methods ignore the influence of the non-uniform water depth and only consider the transport of inert materials, hence the inability of modelling biochemical reactions. In addition, the existing applications mainly focus on instantaneous-release problems, where a fixed number of particles move in the computational domain. This paper first presents examples to showcase the capability of a newly-developed random-walk model in simulating the continuous sources of non-conservative substances. Then, the method is applied to examine the BOD-DO balance along a hypothetical river. The predictions agree well with analytical solutions. Finally, the developed model is used to study the pollutant transport in the Thames Estuary. The current model is illustrated to be able to accurately predict the interaction between multiple pollutants in real-world situations with uneven bathymetry and extensive intertidal floodplains. Highlights: We develop a depth-averaged random walk model for water quality modelling. It can model the continuous release of multiple non-conservative pollutants. We demonstrate its good performance in real-world applications.